2021
DOI: 10.3389/fenvs.2021.678574
|View full text |Cite
|
Sign up to set email alerts
|

Physisorption and Chemisorption Mechanisms Influencing Micro (Nano) Plastics-Organic Chemical Contaminants Interactions: A Review

Abstract: Microplastics, which serve as sources and vector transport of organic contaminants in both terrestrial and marine environments, are emerging micropollutants of increasing concerns due to their potential harmful impacts on the environment, biota and human health. Microplastic particles have a higher affinity for hydrophobic organic contaminants due to their high surface area-to-volume ratio, particularly in aqueous conditions. However, recent findings have shown that the concentrations of organic contaminants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 257 publications
(353 reference statements)
1
46
0
1
Order By: Relevance
“…Many of these plastic particles are made of polyethylene, but the number of studies monitoring the fragmentation process is limited. Nevertheless, recent studies reported that weathering and some other processes, particularly the exposure of UV radiation in the presence of oxygen, can be the key players of the fragmentation of polyethylene films [ 7 , 14 ]. The deterioration of various plastic litter or discarded plastic products may occur by physical, chemical and biological processes, releasing plastic particles to the environments [ 2 ].…”
Section: What Is a Plastic Particle?mentioning
confidence: 99%
“…Many of these plastic particles are made of polyethylene, but the number of studies monitoring the fragmentation process is limited. Nevertheless, recent studies reported that weathering and some other processes, particularly the exposure of UV radiation in the presence of oxygen, can be the key players of the fragmentation of polyethylene films [ 7 , 14 ]. The deterioration of various plastic litter or discarded plastic products may occur by physical, chemical and biological processes, releasing plastic particles to the environments [ 2 ].…”
Section: What Is a Plastic Particle?mentioning
confidence: 99%
“…Plastic materials have been reported to have high sorption capacity with hydrophobic organic chemicals (HOCs) [ 34 ]. Therefore, the labelling of NPTs was performed by taking advantage of the hydrophobic interactions that occur between their surface and HOCs [ 35 ]. Lead (II) phthalocyanine (PbPc) is an aromatic hydrophobic organic compound chosen for its hydrophobicity and its capability to be quantified through SP-ICP-MS by monitoring the lead included inside the compound.…”
Section: Labelling Strategiesmentioning
confidence: 99%
“…While primary microplastics are originally manufactured for use in cosmetics, toothpaste, or pharmaceutical drugs (Mintenig et al, 2017), secondary microplastics, on the other hand, exist from the degradation of larger plastics into smaller pieces under different chemical, physical, and biological conditions (Horton et al, 2017a;Padervand et al, 2020;Agboola and Benson, 2021). The steady rise in the production and use of plastics led to an increase in presence of microplastics in the environment (Cole et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The steady rise in the production and use of plastics led to an increase in presence of microplastics in the environment (Cole et al, 2011). MPs are found in a variety of everyday products, including facial scrub cleansers, sea salts, and toothpastes (Chang, 2015;Zhang et al, 2020a;Agboola and Benson, 2021). MPs enter aquatic ecosystems by a variety of routes, the most common of which being surface runoff, air currents, and wastewater treatment plants (WWTPs) effluent (Dris et al, 2015;Turan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%